Pengaruh POC Dan AB MIX Terhadap Pertumbuhan Dan Hasil Tanaman Pakchoy (Brassica chinensis L.) Dengan Sistem Hidroponik - Sundari, Sundari; Raden, Ince; Hariadi, Untung Slamet (Jurnal Magrobis, 2016)
The purpose of this study to determine the effect of POC and AB Mix on the growth and yield of pakchoy. This research was conducted in February and March 2016. Starting from seeding to harvest. Research located in the village Sepakat, District Tenggarong Seberang, Kutai Kartanegara. The study used a randomized block design (RAK) with factorial analysis 2 with repetition as much as (3). The treatment is a liquid organic fertilizer (P), which consists of 4 levels, namely p0 (control), p1 (5 ml POC L-1 water), p2 (10 ml POC L-1 water), p3 (15 ml POC L-1 water) and provision of AB Mix (N), which consists of 4 levels, namely n0 (control), n1 (AB Mix 600 ppm), n2 (AB Mix 1,200 ppm), n3 (AB Mix 1,800 ppm). The results showed that treatment of liquid organic fertilizer results showed no significant effect on all parameters but treatment provision Mix AB showed a highly significant effect on all parameters with results of the highest weight at treatment plants n3 (AB Mix 1,800 ppm).Keyword : Hydroponik, pakchoy, AB mix